2013
DOI: 10.1016/j.compfluid.2012.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Wall orientation and shear stress in the lattice Boltzmann model

Abstract: The wall shear stress is a quantity of profound importance for clinical diagnosis of artery diseases. The lattice Boltzmann is an easily parallelizable numerical method of solving the flow problems, but it suffers from errors of the velocity field near the boundaries which leads to errors in the wall shear stress and normal vectors computed from the velocity. In this work we present a simple formula to calculate the wall shear stress in the lattice Boltzmann model and propose to compute wall normals, which are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 47 publications
(51 reference statements)
0
22
0
Order By: Relevance
“…Although the grid-based normal n j is appropriate for extrapolating S αβ from the computational nodes to the boundary points, the normal used to find the components in equation (18) was based on the local wall geometry as N j · B j = 0, where B j = b j+10 − b j−10 is a measure of the local surface. The value of 10 was selected to give a smooth measure of the surface, and is comparable to the value used in [41]. Figure 9 shows the Peak WSS (PWSS) on the stenosed regions of the outer ECA and ICA walls.…”
Section: Resultsmentioning
confidence: 99%
“…Although the grid-based normal n j is appropriate for extrapolating S αβ from the computational nodes to the boundary points, the normal used to find the components in equation (18) was based on the local wall geometry as N j · B j = 0, where B j = b j+10 − b j−10 is a measure of the local surface. The value of 10 was selected to give a smooth measure of the surface, and is comparable to the value used in [41]. Figure 9 shows the Peak WSS (PWSS) on the stenosed regions of the outer ECA and ICA walls.…”
Section: Resultsmentioning
confidence: 99%
“…[34][35][36] When simulating systolic blood flow in the abdominal aorta and mesenteric artery using both FEM and LBM, it was found that the LBM is as accurate as FEM for solving complex blood flows. 38,39 Therefore, using the LBM is appropriate for high resolution 3D simulations. 36 LBM was found to have improved cost per time step, code implementation, and parallelization.…”
Section: Discussionmentioning
confidence: 99%
“…37 Chapman-Enskog analysis furthermore showed that LBM reproduces the incompressible Navier-Stokes equations. 38,39 Therefore, using the LBM is appropriate for high resolution 3D simulations.…”
Section: Discussionmentioning
confidence: 99%
“…An in-house developed massively parallel CFD code, HARVEY, was used to simulate hemodynamics in the 3 computational models. 19,25,24,32 The hemodynamics solver HARVEY uses an implementation of the lattice Boltzmann method (LBM) to solve the Navier-Stokes equations governing fluid flows in complex 3D geometries. 3,17,36 Discretizing space and velocity with a fixed Cartesian lattice, LBM models the fluid with a particle distribution function , which denotes the probability of finding a particle at time t and lattice point with the discrete velocity .…”
Section: Cfd Simulations Using Harveymentioning
confidence: 99%
“…To compute the WSS vector , the stress tensor σ αβ is computed from the nonequilibrium distribution: . Using the approach from Matyka et al, 19 the outward nor- mal vector is estimated, and the WSS vector components are computed as . Additional details about the HARVEY implementation, parallelization, and scaling may be found in the articles by Randles et al 24,25 TAWSS and OSI are defined as: 21 where represents the instantaneous WSS vector and T is the period of the cardiac cycle.…”
Section: Cfd Simulations Using Harveymentioning
confidence: 99%